Timely initiation of new antenatal care contact model and its associated factors among pregnant women at Munessa health facilities, Ethiopia: a facility-based cross-sectional study - Hailu, Efirem; Bekele, Daniel; Megersa, Getu (Frontiers in Medicine, 2025)
BackgroundThe new antenatal care (ANC) contact model is recommended to be initiated within the first trimester of pregnancy, specifically before 12 weeks of gestation. The health of expectant mothers and the unborn children can be improved by early identification and treatment of preexisting and pregnancy-related conditions. However, in Ethiopia, there is limited evidence to support this. This study aimed to evaluate the extent of timely initiation, knowledge, attitude, and related aspects toward the new ANC contact model among pregnant women attending Munessa Health facilities.MethodsA cross-sectional study was carried out in a facility with 482 participants between April and May of 2024. The necessary sample was chosen by the use of a systematic sampling technique. Data were gathered from pregnant women who were visiting the prenatal care facility using an interviewer-administered questionnaire. Data were coded and entered using Epidata version 3.1 and analyzed by SPSS version 25. Binary and multivariable logistic regression analyses were used to identify possible determinants, and an odds ratio was used to measure the strength of associations at a p-value of <0.05.ResultsThe study revealed that 127 (26.5%) women initiated ANC on time. Generally, 215 (44.8%) pregnant women had a positive attitude toward and 83 (17.3%) of them had good knowledge of the new ANC contact model. Attending non-formal learning (AOR, 0.094, 95% CI 0.13, 0.56), being tested for pregnancy by urine (AOR, 6.4; 95% CI: 3.51, 12.03), having had no prior history of abortion (AOR = 0.47; 95% CI: 0.23, 0.97), and having no history of ANC complications (AOR = 0.076, 95% CI 0.03, 0.06) were significantly associated with the timely initiation of ANC contact.ConclusionThis study highlights the significance of exerting considerable effort to expand the coverage of timely ANC initiation. Consequently, raising mothers’ attitudes and level of awareness about ANC services and pregnancy hazard signals is crucial for expanding the coverage of timely ANC contact initiation.